2020
DOI: 10.7759/cureus.8294
|View full text |Cite
|
Sign up to set email alerts
|

Alexandrite Laser-Induced Choroidal Neovascularization Successfully Treated With Aflibercept

Abstract: A 33-year-old female was referred to the ophthalmology department after an accidental eye injury to her right eye during a hair removal session using alexandrite laser. Although she initially experienced no symptoms, when reexamined one and a half months later the bestcorrected visual acuity (BCVA) of the affected eye was 20/40 secondary to choroidal neovascularization confirmed by fluorescein angiography (FA) and optical coherence tomography (OCT). Intravitreal anti-vascular endothelial growth factor (VEGF) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…As a consequence of chorioretinal anastomoses, in some cases, choroidal neovascular membranes may develop. 10,11 In the current case, no signs of choroidal neovascularisation were evident during six months.…”
Section: Np56mentioning
confidence: 47%
“…As a consequence of chorioretinal anastomoses, in some cases, choroidal neovascular membranes may develop. 10,11 In the current case, no signs of choroidal neovascularisation were evident during six months.…”
Section: Np56mentioning
confidence: 47%
“…Several studies reported similar results for the use of IVA in cases of CNV secondary to trauma, laser-induced retinal injury, uveitis, and hereditary disorders. Diafas et al [ 9 ] reported a complete resolution of CNV secondary to laser pointer injury using a single IVA injection. They had no recurrences over 38 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Laser operators should report novel adverse events in the literature and share them with the medical community. 107 -139…”
Section: Discussionmentioning
confidence: 99%